Modifikasi Contrast Wheel pada Carousel Keberangkatan di Bandar Udara Internasional I Gusti Ngurah Rai - Kurnianto, Benny; Mediaswati, Cristina Novi; Alexander, Aldrian; Alfianto, Galih; Latifa, Faza Nuha; Putra, Okky Dirgantara (Program Studi Teknik Mekanikal Bandar Udara, 2023)
Conveyors are a key component in the baggage transportation process at the airport, and bearings play an important role in maintaining optimal performance. Often there is a problem with the release of Polyurethane rubber from the bearing that occurs in the Pressure Roller. In this study, the level 1 R&D research method was used by utilizing 3D modeling simulations to analyze the effect of bearing modifications on conveyor performance. By modifying the bearings on the conveyor at I Gusti Ngurah Rai Airport, this research aims to increase the efficiency of the baggage handling system. The results of this study provide practical recommendations for the implementation of bearing modifications on conveyors at other airports with the aim of increasing operationa performance and efficiency. The results of this research can also become the basis for developing a more efficient baggage handling system at other airports